Analysis of Features in The Design of Small-Dimensioned Robots - Starikova, S.; Karpenko, I. (My University, 2024)
Analysis of features in the design of small-sized robots reveals key aspects related to their mobility, energy efficiency and flexibility. The design of such robots requires weight and size optimization, which allows them to be used in narrow spaces and difficult conditions. This opens up new opportunities for the use of small-sized robots in specialized industries where high maneuverability and precision are required.
Keywords: Industry 4.0; small robots